2014
DOI: 10.1007/s11743-014-1579-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect on Wettability of Mixtures of Amine Oxides, Alkylpolyglucosides, and Ethoxylated Fatty Alcohols

Abstract: The mixture proportions of three surfactants, i.e. an alkylpolyglucoside (APG), an ethoxylated fatty alcohol, and an amine oxide (AO), were optimized by applying Response Surface Methodology in order to achieve the surfactant ratio that produces the highest wetting power. The synergistic effect of the binary samples of AO with the other surfactants was firstly verified. An improvement in this synergistic effect on wettability was found in the ternary mixture. In the experimental range analyzed, the surfactant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…As expected, the N ‐oxide sugar‐derived surfactants showed better water solubility in comparison to the N ‐oxide surfactant LA. Previous studies have shown an improved solubility by the introduction of an N ‐oxide functional group [32] . This also applies for the comparison of N ‐GalA1.12 and its starting material GalA1.12 , [26,27] which have a solubility of 7 % and 1 %, respectively.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…As expected, the N ‐oxide sugar‐derived surfactants showed better water solubility in comparison to the N ‐oxide surfactant LA. Previous studies have shown an improved solubility by the introduction of an N ‐oxide functional group [32] . This also applies for the comparison of N ‐GalA1.12 and its starting material GalA1.12 , [26,27] which have a solubility of 7 % and 1 %, respectively.…”
Section: Resultsmentioning
confidence: 73%
“…Previous studies have shown an improved solubility by the introduction of an N-oxide functional group. [32] This also applies for the comparison of N-GalA1.12 and its starting material GalA1.12, [26,27] which have a solubility of 7 % and 1 %, respectively. Overall, the bio-based surfactants derived from monosaccharides showed promising surfactant properties.…”
Section: Resultsmentioning
confidence: 99%